Ground handling business at non-European biggest world airports as a problem of market structures - Tomová, Anna; Trgiňa, Lukáš; Novák Sedláčková, Alena (Business, Management and Economics Engineering, 2015)
In the paper we analyse the market structures of ground handling at the biggest non-European passenger and cargo airports in accordance with the ACI list of the most important world airports in 2014. Using the IATA IGHC database as of spring 2015, our analysis revealed that out of Europe double digit numbers of providers are rare what contrasts with situation in Europe where ground handling markets were deregulated by the Council Directive 96/67/EC. The analysis also brought that the monopolistic structures of ground handling markets were more specific for the regions of Asia and the Middle East. Airports as ground handling providers were not found within the analysed sample in North America, Latin America, Africa and Australia and Oceania, while this arrangement was to a larger extent present at the analysed Asian airports. Asia and the Middle East biggest airports are identified by us as candidates for further deregulation of ground handling arguing by forecasted demand for air services in the regions, although expected deregulation may be curbed by national regulators.